The role of the trunk control in athletic performance of a reactive change-of-direction task - Edwards, S.; Austin, A. P.; Bird, S. P. (The Journal of Strength and Conditioning Research, 2017)
Agility is vital to success in team sport competition with the trunk argued to play a key role in sport performance. This study explored the role of trunk control during a reactive change-of-direction task (R-COD) and field-based measures of athletic performance. Twenty male players completed field-based athletic performance assessments (modified Illinois agility test [mIAT], 3 repetition maximum back squat, and 5 countermovement jumps [CMJ]) and R-CODs, during which 3-dimensional ground reaction forces and kinematics were recorded. Trunk control was assessed as the sum of the trunk relative to the pelvis range of motion (ROM) in all 3 planes during the R-COD. Participants with the highest (HIGH, n = 7) and lowest (LOW, n = 7) trunk ROM values were grouped. The HIGH group achieved significantly shorter mIAT time duration, higher CMJ height, and lower knee flexion angles, greater trunk lateral flexion and rotation relative to pelvis, and greater angular momentum during the R-COD compared with the LOW group. Superior athletic performance was associated with decreased trunk control (high trunk ROM) during the R-COD. Although this study suggested that trunk control is a vital component of performance, it is unknown whether this trunk control is inherent or an effect of training history, nor does not support current optimal athletic performance recommendation of decreased trunk motion during R-COD.